2008
DOI: 10.1243/09544119jeim371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serum deprivation on the mechanical properties of adherent vascular smooth muscle cells

Abstract: Vascular smooth muscle cell (VSMC) function plays a key role in regulating the development and progression of vascular lesions. Among the more significant phenomena that occur during the development of these lesions is the phenotypic switching of VSMCs from a contractile to a synthetic state. A better understanding of the concurrent changes to VSMC mechanical properties that occur with phenotypic shifts can help to elucidate the role of VSMC mechanics in the development of vascular diseases. In the current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…However, in that case the stiffness mismatch of materials was a factor of 10 (i.e., mechanical stiffness properties of calcifications were 10 times greater than those of the surrounding fibrin cap). Within our gels, the mismatch of cell and hydrogel stiffnesses is probably not as drastic, as evidenced by previous mechanical characterizations (7,19,36). Browning et al (7) uniaxially strained PEGDA hydrogel rings and calculated a secant modulus of stress-strain data, which yielded a value of 19 kPa for 20% concentration, 10-kDa molecular mass gels as used here.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, in that case the stiffness mismatch of materials was a factor of 10 (i.e., mechanical stiffness properties of calcifications were 10 times greater than those of the surrounding fibrin cap). Within our gels, the mismatch of cell and hydrogel stiffnesses is probably not as drastic, as evidenced by previous mechanical characterizations (7,19,36). Browning et al (7) uniaxially strained PEGDA hydrogel rings and calculated a secant modulus of stress-strain data, which yielded a value of 19 kPa for 20% concentration, 10-kDa molecular mass gels as used here.…”
Section: Discussionsupporting
confidence: 68%
“…Browning et al (7) uniaxially strained PEGDA hydrogel rings and calculated a secant modulus of stress-strain data, which yielded a value of 19 kPa for 20% concentration, 10-kDa molecular mass gels as used here. The apparent elastic moduli of rat aortic SMCs and murine embryonic cells have been measured by atomic force microscopy (AFM) indentation in the respective ranges of 10 -25 kPa and 0.5-16 kPa, depending on level of serum deprivation or differentiation state (19,36). Thus, in our case, although the stiffnesses of 10T1/2 cells and PEGDA hydrogels are certainly not identical, they are probably within the same order of magnitude.…”
Section: Discussionmentioning
confidence: 68%
“…In that study, cell stiffness by AFM did not change significantly in the setting of serum starvation, which the authors attributed to compensatory compaction of intermediate filaments around the nucleus. In fact, Hemmer et al 9. reported that serum starvation increases the AFM-measured stiffness of vascular smooth muscle cells, which they suggested may be secondary to serum-induced changes in shape and spreading area.…”
Section: Discussionmentioning
confidence: 99%
“…As the modulus is an internal cellular property that depends largely on the cytoskeleton structure, it should not be affected by tip coating such as the serum protein corona. As all cells were cultured under identical conditions, those incubated in serum and those without serum during the measurements should have the same overall modulus; indeed, it has been shown49 that the presence or absence or serum proteins does not affect the overall cell modulus over periods shorter than 3 days. We thus extracted the effective modulus E* = 1.3 kPa of our cells from the Group I results as noted above, and attempted to use this value for fitting the data of group II, as it appears in Fig.…”
Section: Resultsmentioning
confidence: 99%